1978
DOI: 10.1002/bit.260200703
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic media for production of quality xanthan gum in 20 liter fermentors

Abstract: SummaryXanthan gum is a heteropolysaccharide synthesized by Xanrhomonas cumpestris NRRL B-1459 and is composed of D-glucose, D-mannose, and D-glucuronic acid, in addition to acetic and pyruvic acids. Different amounts of pyruvic acid ketal are found in various preparations which can influence the viscosities of dilute xanthan solutions. Polysaccharide production on synthetic media was studied in small-scale fermentors. Fermentation conditions were established for production of both high and low pyruvic acid gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
14

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 10 publications
2
17
0
14
Order By: Relevance
“…Durante o período de inoculação, ocorre um aumento da concentração celular, mas diminui a produção de goma xantana, porque a goma ao redor da célula impede o transporte de nutrientes e extende a fase lag de crescimento (Cadmus et al, 1978;De Vuyst et al, 1987;Pons et al, 1989;Pons et al, 1990).…”
Section: Inóculounclassified
See 2 more Smart Citations
“…Durante o período de inoculação, ocorre um aumento da concentração celular, mas diminui a produção de goma xantana, porque a goma ao redor da célula impede o transporte de nutrientes e extende a fase lag de crescimento (Cadmus et al, 1978;De Vuyst et al, 1987;Pons et al, 1989;Pons et al, 1990).…”
Section: Inóculounclassified
“…As variáveis estudadas no trabalho de Casas et al (2000) são principalmente aquelas que mostram influência no conteúdo de ácido pirúvico. A influência da temperatura tem sido estudada somente para o grau de piruvação, e todos os autores acreditam que o conteúdo de piruvato máximo é obtido em 27°C (Cadmus et al, 1978;Tako e Nakamura, 1984;Shu e Yang, 1990;Peters et al, 1993).…”
Section: Meio Nutriente Para a Produção Da Goma Xantanaunclassified
See 1 more Smart Citation
“…In continuous fermentation, this pyruvic acid to acetic acid ratio and molecular weight increased with an increase in citric acid concentration in feed. High agitation and aeration has been reported to increase pyruvic acid content in xanthan (Cadmus et al, 1987). This study showed that citric acid increases the pyruvic acid content both in aerobic and oxygen-limited conditions.…”
mentioning
confidence: 52%
“…A produção de xantana tem sido avaliada na faixa de temperatura de 20 a 38 °C (CADMUS et al, 1978;GUPTE;KAMAT, 1997;LEELA;SHARMA, 2000). A maioria dos autores estabeleceu 28 °C como temperatura ótima de produção de xantana.…”
Section: Ph E Temperaturaunclassified